The Remote Control Car System using Bluetooth HC-05 with Android Smartphone - Muhammad sudrajat; Rahmat Hidayat (Sultan Publisher, 2023)
Remote control car is a miniature car with a smaller size, which is controlled directly by remote or joystick using the HC-05 bluetooth module with the android smartphone application. Making a remote control car using Wemos R1 D1 as a microcontroller and four DC motors to drive the wheels of a remote control car. At this writing it was done to test the remote control car system with an application created using the MIT APP Inventor. In this test it was found that the remote control car system can work well at a distance of 0-20 meters and there is a difference in delay for each command used.